Sanctuaries of Earth, Stone, and Light : The Churches of Northern New Spain, 1530-1821 - Giffords, Gloria Fraser, 1938- (Book collections on Project MUSE., 2007)
"Over nearly three centuries, Jesuit, Franciscan, and Dominican missionaries built a network of churches throughout the vast region known as New Spain, paving the way for later cathedrals and parochial churches. Since the early twentieth century, scholars have studied the colonial architecture of southern New Spain, but they have largely ignored the architecture of the north. However, as this book clearly demonstrates, the colonial architecture of northern New Spain - an area that encompasses most of the southwestern United States and much of northern Mexico - is strikingly beautiful and rich with meaning. After more than two decades of research, both in the field and in archives around the world, Gloria Fraser Giffords has authored the definitive book on this architecture." "Giffords has a remarkable eye for detail and for images both grand and diminutive. Because so many of the buildings she examines have been destroyed, she sleuthed through historical records in several countries and discovered that the architecture and material culture of northern New Spain reveal the influences of five continents. As she examines objects as large as churches or as small as ornamental ceramic tiles, she illuminates the sometimes subtle, sometimes striking influences of the religious, social, and artistic traditions of Europe (from the beginning of the Christian era through the nineteenth century), of the Muslim countries ringing the Mediterranean (from the seventh through the fifteenth centuries), and of northern New Spain's indigenous peoples (whose art influenced the designs of occupying Europeans)."--Jacket.